Historia literatury w objęciach Darwina? - Skórczewski, Dariusz (Colloquia Litteraria, 2011)
History of literature held in darwin’s embrace? The paper adumbrates Joseph Carroll’s evolutionist literary theory positioning it against the developments in literary studies and humanities after postmodernism. The author discusses the ambivalence present in Carroll’s neo-darwinian project, its possible power to revert the decline of literary studies through a return to tangibility and certainty after the dominance of postmodern speculative theories, but also its reductionist and anti-axiological- stance being a peril to the advancement of literary studies. The paper invites further discussion on the prospects of trans-disciplinary alliance between humanities and biological sciences in relation to the aesthetic specificity of literature.